The portfolio choices of Hispanic couples - Deborah A. Cobb-Clark; Vincent A. Hildebrand (Institute for the Study of Labor (IZA), 2006)
This paper analyzes the portfolio allocations of couple-headed, Hispanic families using Survey of Income and Program Participation (SIPP) data. Our results reveal that Hispanic couples as a group are less wealthy than otherwise similar white couples, although there is substantial variation across Hispanic-origin groups. Much of the disparity in portfolio choices of Hispanics relative to whites appears to stem from these lower wealth levels. Accounting for these wealth disparities, Hispanic couples hold less financial wealth, but more real estate and business equity than do white couples.
Keywords: J61; G11; J10; 330; portfolio choices; Hispanic